Synthesis of branched inner-core oligosaccharides of neisserial lipooligosaccharides. (10th September 2021) - Ichiyanagi, Tsuyoshi; Narimoto, Hirofumi; Ohtani, Naoki
Abstract: In this study, branched inner-core oligosaccharides of neisserial lipooligosaccharides was successively synthesized. We found that the glycosylation of a 4- O -substituted heptose derivative with a heptosyl donor proceeded smoothly proceeded in toluene and provided corresponding 3, 4-di- O -substituted heptose as a single diastereomer. In addition, we found that the fragment condensation of a 3, 4-di- O -substituded heptosyl donor with the axially oriented 5-position of a 4- O -substituted Kdo acceptor provided a consecutive branched hexasaccharide with a vicinal trans -diol of l - glycero -d - manno -heptose (Hep) and a vicinal cis- diol of 3-deoxy-d - manno -oct-2-ulosonic acid (Kdo) in its structure. Graphical abstract: Image 1